Effect of anaesthesia on cell-mediated immunity in dogs undergoing mastectomy for mammary cancer. (May 2022) - Karayannopoulou, Maria; Anagnostou, Tilemachos; Margariti, Apostolia; Kritsepi-Konstantinou, Maria; Psalla, Dimitra; Savvas, Ioannis; Kazakos, Georgios
Abstract: Objective: To investigate if anaesthesia for canine cancer mastectomy further influences host cell-mediated immunity (CMI) promoting cancer progression. Study design: A randomized, controlled, blinded clinical study. Animals: A total of 20 bitches with malignant mammary tumours of clinical stage II or III undergoing the same type of mastectomy (regional mastectomy). Methods: Dogs were randomly allocated to one of two anaesthetic groups (10 per group). The anaesthetic protocol of group A used minimally immunosuppressive drugs (tramadol, robenacoxib, propofol), whereas that of group B (control) used more immunosuppressive drugs (morphine, fentanyl, thiopental, isoflurane). For each animal, measurements of white blood cells (WBCs), neutrophils and lymphocytes, and flow cytometric assessment of T cells (CD3 + ), helper T cells (CD4 + ), cytotoxic T cells (CD8 + ) and CD5 low+ T cells were performed prior to anaesthesia (day 0) and on days 3 and 10 postsurgery. Data were analysed using a General Linear Model for repeated measures and presented as mean ± standard deviation, p ≤ 0.05. Results: In all animals, on day 3, WBCs and neutrophils were significantly increased ( p < 0.0005), while flow cytometry revealed significantly decreased relative percentages of T cells (CD3 + ) ( p  = 0.003) and their subpopulations CD4 + ( p  = 0.006), CD8 + ( p  = 0.029) and CD5 low+ ( p  = 0.031). Specifically, on day 3, the cytotoxic T cells (CD8 + ) were significantly decreased ( p  = 0.05) only in group B, whereas the CD4 + ( p  = 0.006) and CD5 low+ ( p  = 0.008) T cells in group A. The only significant difference between groups was found preoperatively in the CD4 + /CD8 + ratio, which was higher in group A ( p  = 0.006). Conclusions and clinical relevance: In dogs with mammary cancer undergoing regional mastectomy, a significant decrease in components of CMI was observed on day 3 postsurgery in both anaesthetic groups. Some indication, however, for better preserved cellular immunity by less immunosuppressive anaesthetic/analgesic drugs was detected, rendering their use advisable.